Effects of aerosolized histamine and carbachol in the conscious horse. - Mirbahar, K B (1985)
Pulmonary function tests were performed in seven conscious, standing horses. Changes in pulmonary mechanics and ventilation volumes were measured after inhalation challenge with saline (baseline), histamine (1% w/v solution for 5 min) and carbachol (0.5% w/v solution for 3 min). Comparisons between baseline and posthistamine values revealed a significant (P less than 0.05) increase in nonelastic work of breathing (Wb), maximum change in transpulmonary pressure (max delta Ppl), and pulmonary resistance (RL), while dynamic compliance (Cdyn) decreased (P less than 0.05). Tripelennamine completely abolished these histamine induced changes suggesting the involvement of H1 receptors. A nonsignificant increase occurred in functional residual capacity. However, the amount of nitrogen retained in the lung at the end of a nitrogen washout test was significantly (P less than 0.05) greater after histamine when compared to baseline values. The effect of carbachol was qualitatively similar to that of histamine, Wb and max delta Ppl increased while Cdyn decreased (P less than 0.05). The increase in lower RL reached statistical significance (P less than 0.05) only at the beginning of expiration (/ 25% VT). The present investigation demonstrates that the physiological measurements of lung function could be carried out in conscious, unsedated horses and that the pulmonary function test methods could be used as a tool for study of drug induced changes in pulmonary mechanics.